Mediational role of perceptual styles in L2 lexical inferencing and the associated strategy use - Zarei, Gholam Reza; Pourghasemian, Hosein (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2016)
Due to the critical role that perceptual learning styles as indicators of individual differences play in L2 learners' activities and thus their academic achievement, the present investigation was aimed to study the role of L2 learners' perceptual styles in lexical inferencing and also the strategies used for lexical inferences in the Iranian context of English language learning. To this end, 134 participants majoring in different engineering fields took part in the study. They received strategy training on how to infer the meanings of unfamiliar words. They then answered a perceptual styles preferences questionnaire and were tested on the selected texts for lexical inferencing. They were asked to extract the meaning of unfamiliar words and simultaneously identify the relevant strategy employed for lexical inferencing by marking it on the strategy questionnaire. The analysis identified the biggest number of participants as being kinesthetic despite the fact that classes were mainly held through audio-visual activities. The findings also showed a meaningful difference between group categories of styles preferences and their lexical inferencing ability (F=4.57, p<.05). As for the modifying effect of perceptual styles on the strategies used by various groups of learners, 'visual learners' were found to have the highest correlation with ‘syntactic knowledge analysis’ (r=.70, p=.01). The results of the study point to the importance of individual differences in the perception of and interaction with the learning environment.